The value -3/7 falls into the category of Rational Numbers. This category includes all numbers that can be expressed as a fraction or quotient of two integers.
Explanation:The value -3/7 belongs in the group of Rational Numbers. Rational numbers are defined as any number that can be represented as the quotient or fraction p/q of two integers, with the denominator q not equal to zero. Integers and Natural numbers, option A and B, do not include negative values or fractions. An irrational number, option D, cannot be written as a simple fraction. Since -3/7 is a negative fraction, it can only be classified as a rational number. So, -3/7 would be placed in the section representing Rational Numbers on a Venn diagram of number types.
Learn more about -3/7 here:https://brainly.com/question/390300
#SPJ12
the number of perfect squares fro 4 to 50 is
Step-by-step explanation:
4, 9, 16, 25, 36,49
there are 6 perfect squares from 4 to 50
Answer:
Perfect squares from 4 to 50 are 4, 9, 16, 25, 36, and 49 .
So there are 6 perfect squares.
Step-by-step explanation:
2 * 2 = 4
3 * 3 = 9
4 * 4 = 16
5 * 5 = 25
6 * 6 = 36
7 * 7 = 49
Follow the steps to solve this equation:
−2x + 6x − 8 = 12
Step 1: Combine like items.
Step 2: Undo the subtraction.
Step 3: Undo the multiplication.
4x − 8 = 12
4x − 8 + 8 = 12 + 8
4x = 20
4
4
x =
20
4
x =???
Answer: x = 5
Step-by-step explanation:
[tex]-2x+6x-8=12\\4x-8=12\\4x=20\\x=\frac{20}{4}\\ x=5[/tex]
Over what interval is the graph of f(x) = –(x + 8)2 – 1 decreasing?
(negative 8, infinity)
(8, infinity)
(negative infinity, 8)
(negative infinity, negative 8)
Answer:
A. -8, infinity
Step-by-step explanation:
2020 edg
Using quadratic function concepts, it is found that the function is decreasing over the interval (-8, infinity).
What is the equation of a parabola given it’s vertex?The equation of a quadratic function, of vertex (h,k), is given by:
[tex]y = a(x - h)^2 + k[/tex]
In which a is the leading coefficient, determining the behavior of the function as follows.
If a > 0, it decreases for (-infinity, h) and increases for (h, infinity).If a < 0, it increases for (-infinity, h) and decreases for (h, infinity).In this problem, the equation is given by:
[tex]f(x) = -(x + 8)^2 - 1[/tex]
Hence the coefficients are a = -1 < 0, h = -8, k = 1, meaning that the function is decreasing over the interval (-8, infinity).
More can be learned about quadratic function concepts at https://brainly.com/question/24737967
You can solve the equation 3x + 3 = x + 5 by graphing y = 3x + 3 and y = x + 5 and finding their point of intersection. Use the drop-down menu to complete the statement below.
The solution of 3x + 3 = x + 5 is:
A. 6
B.1
C.(1,6)
D. (6,1)
Answer:
The answer is 1.
Step-by-step explanation:
The correct option is B. [tex]1[/tex]. The solution to [tex]\(3x + 3 = x + 5\)[/tex] is [tex]\(x = 1\)[/tex]
To solve the equation [tex]\(3x + 3 = x + 5\)[/tex] by graphing [tex]\(y = 3x + 3\)[/tex] and [tex]\(y = x + 5\)[/tex], we need to find their point of intersection.
1. Graphing the Equations:
The first equation is [tex]\(y = 3x + 3\)[/tex], which has a slope of [tex]3[/tex] and a y-intercept of [tex]3[/tex].
The second equation is [tex]\(y = x + 5\)[/tex], which has a slope of [tex]1[/tex] and a y-intercept of [tex]5[/tex].
2. Finding the Intersection:
Plot the two lines on the graph.
The point where the two lines intersect is the solution to the equation [tex]\(3x + 3 = x + 5\)[/tex]
From the graph provided:
The two lines intersect at the point [tex]\((1, 6)\)[/tex]
3. Verifying the Solution:
Substitute [tex]\(x = 1\)[/tex] into the original equation[tex]\(3x + 3 = x + 5\)[/tex]
[tex]\[ 3(1) + 3 = 1 + 5 \\ 3 + 3 = 6 \\ 6 = 6 \][/tex]
The solution is verified.
Therefore, the solution to [tex]\(3x + 3 = x + 5\)[/tex] is [tex]\(x = 1\)[/tex]
The complete question is
You can solve the equation 3x+3=x+5 by graphing y=3x+3 and y=x+5 finding their point of intersection. and Use the drop-down menu to complete the statement below. The solution of 3x+3=x+5 is
A. 6
B. 1
C. (1,6)
D. (1,1)
claris brought 8 tickets for a total cost of $104. she had used a coupon code to get $3 off each ticket. let x be the original cost of each ticket. write an equation that correctly represents the situation.
Answer:
8 = 104 - 3x
Step-by-step explanation:
A sidewalk around a circular garden is 3 feet wide what is the area of the sidewalk
We can see here that the area of the sidewalk surrounding the circular garden is approximately 216.66 ft².
To find the area of the sidewalk surrounding the circular garden, we need to calculate the difference between the area of the larger circle and the area of the smaller circle.
The radius of the circular garden is given as 10 ft. The radius of the garden plus the sidewalk is equal to the sum of the radius of the garden and the width of the sidewalk. Since the width of the sidewalk is 3 ft, the radius of the larger circle (including the sidewalk) is 10 + 3 = 13 ft.
Now, let's calculate the area of the larger circle using the formula A = πr², where A represents the area and r represents the radius. Substituting the values, we have A = 3.14 × (13)² = 3.14 × 169 = 530.66 sq ft.
Next, we calculate the area of the smaller circle (just the garden) using the same formula. A = 3.14 × (10)² = 3.14 × 100 = 314 sq ft.
Finally, we subtract the area of the smaller circle from the area of the larger circle to find the area of the sidewalk. 530.66 - 314 = 216.66 sq ft.
Therefore, the area of the sidewalk surrounding the circular garden is approximately 216.66 square feet.
The complete question is:
A sidewalk that is 3 ft wide surrounds a circular garden with a radius of 10 ft. What is the area of the side walk? use pi=3.14
Find A U C.
A) {2,3,5,6,7,9,11}
B) {3,5,6,7,8,11,12}
C) {3,5,6,7}
D) {3,5,7}
Answer:
A U C = {2,3,5,6,7,9,11}
Step-by-step explanation:
A = {2,3,5,6,7,9,11}
C = {3,5,6,7}
The union of two sets is a set that has every element that belongs to one or the other set.
A U C = {2,3,5,6,7,9,11}
What’s 2x+4 equal because I’ve been thinking what it was
Hope this will help u....
Answer:
0
Step-by-step explanation:
2x+4
x= -4/2
x= -2
2(-2)+4
-4+4
= 0
On Tuesday, Franklin deposited $35 into his account. On Wednesday, he withdrew $25. Evaluate the expression ⎪35⎥ - ⎪-25⎥ to find the net change of his account.
Question 7 options:
A:10
B:-10
C:None of the Above
D:60
The net change of Franklin's account is 10.
Explanation:Subtraction is a fundamental arithmetic operation that involves finding the difference between two numbers. It is denoted by the minus sign (-). To subtract one number from another, align the digits according to place value and subtract each column, starting from the rightmost column
To find the net change of Franklin's account, we need to evaluate the expression |35| - |-25|.
The absolute value of 35 is 35, and the absolute value of -25 is 25.
Subtracting these values, we have 35 - 25 = 10.
Therefore, the net change of Franklin's account is 10.
Learn more about Net Change of an Account here:https://brainly.com/question/29989249
#SPJ2
The sanitation department calculated that last year each city resident produced approximately 1.643 × 103 pounds of garbage. There are 2.61 × 105 people living in the city. How much garbage did the city sanitation department collect last year?
4.2882 pounds
428.820 pounds
428,820 pounds
428,820,000 pounds
Answer:the last one
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
I just did it!
What is the lcm of 8,12,3
Answer: 24
Step-by-step explanation:
Lowest common multiple means the lowest number that can be divisible by 8,12,3
Looking at this, let's pick 8&3 first
8×3=24
12×3=36
12×8=96
Looking at this value,24 seems to be the lowest,
Therefore the lowest common multiple is 24
If 30% of the people who shop at a local grocery store buy chocolate ice-cream, what is the probability that it will take at least 5 customers to find one who buys chocolate ice-cream?
Heather set up a simulation using a random digits table select one digit numbers where 0-2 is a customer who buys chocolate ice cream and 3-9 is a customer who does not. Keep selecting one digit numbers until you get a 0-2. Record the number of digits selected.
Her results are shown in the table after 15 trials. What is the probability that it will take at least 5 customers to find one who buys chocolate ice cream?
Answer:
A
Step-by-step explanation:
Since you are trying to find the probability that it takes at least five customers count up all the trials where 5 or more numbers were used. Put that number over the total number of trials (15). The correct answer is 4/15
The probability that it will take at least [tex]5[/tex] customers to find one who buys chocolate ice cream is approximately [tex]53.33\%[/tex]
The correct probability that it will take at least [tex]5[/tex] customers to find one who buys chocolate ice cream is the number of trials where it took at least [tex]5[/tex] customers to find a chocolate ice cream buyer divided by the total number of trials.
Let's denote the number of trials where it took at least [tex]5[/tex] customers as [tex]\( A \)[/tex] and the total number of trials as [tex]\( T \)[/tex] The probability [tex]\( P \)[/tex] is then given by:
[tex]\[ P = \frac{A}{T} \][/tex]
From the given data, we have:
[tex]\( A = 8 \)[/tex] (since there are [tex]8[/tex] trials where it took [tex]5[/tex] or more customers)
[tex]\( T = 15 \)[/tex] (since there are [tex]15[/tex] trials in total)
Now, we can calculate the probability:
[tex]\[ P = \frac{8}{15} \][/tex]
This is the probability that it will take at least [tex]5[/tex] customers to find one who buys chocolate ice cream.
To express this probability as a percentage, we multiply by [tex]100[/tex]
[tex]\[ P(\%) = \frac{8}{15} \times 100 = \frac{800}{15} = 53.33\% \][/tex]
Find the zeros of the function f(x)=6(x+2)(x-8.6)
Answer:
1) f⁻1(x)= x+2/123
2) f(0.02235)=0.75
3) x= 0.02235
Step-by-step explanation:
part 1)
given that
f(x)=123x-2
to find F⁻1(x) we put X = f⁻1(x) in the given function to obtain
f(f⁻1(x))=123xf⁻1(x)
-> x+123x f⁻1(x)-2(f(f^-1(f⁻1(x)-x+2/123
part 2 and 3
for f(x)=0.75 we put f(x)=0.75and then solve for "x"
0.75=123 times x-2
x+0.75+2/123=0.02235
Show that (4i)/(-1+i)^18 is real and find its value.
Answer:
- 4/(√2)^18
Step-by-step explanation:
hello : look this solution
Please Help! If (5x-2)^2=ax^2-bx+c, what is the value of a+c^2?
Answer:
The solved problem is in the photo. Hope it helps.
The value of a, b, and c is 25, -20, and 4 respectively. Then the value of the expression will be 41.
What is Algebra?Algebra is the study of mathematical symbols and the rule involves manipulating these mathematical symbols.
If (5x - 2)² = ax² - bx + c.
Then the value of the expression will be a + c²
Open the bracket, then we have
(5x - 2)² = 25x² - 20x + 4
Then the value of the a, b, and c will be
a = 25, b = -20, c = 4
Then the value of the expression a + c² will be
→ 25 +4²
→ 41
More about the Algebra link is given below.
https://brainly.com/question/953809
Michael recorded the color of each car that passed by his office. He saw 30 blue cars and 40 green cars. What is the experimental probability that the next car Michael sees will be a blue car?
Answer:
3/7
Step-by-step explanation:
Find the 82nd term of the arithmetic sequence − 10 , 6 , 22
Answer:
The real answer is 1286
Step-by-step explanation:
81x16=1296
(16 is the common difference)
1296-10=1286
What’s the value??????
Answer:
x = -1, x = 3 (B)
Step-by-step explanation:
25ˣ=5ˣ²⁻³
Can be simplified to:
5²ˣ=5ˣ²⁻³
2x=x²-3
x²-2x-3=0
(x-3)(x+1)
x = -1, x = 3
Plz mark my answer as brainiest
Answer:
B x=-1 x=3
Step-by-step explanation:
25^x = 5 ^ (x^2 -3)
Replace 25 by 5^2
5^2^x = 5 ^ (x^2 -3)
We know that a^b^c = =a^(b*c)
5^(2x) = 5 ^ (x^2 -3)
The bases are the same so the exponents must be the same
2x = x^2 -3
Subtract 2x from each side
2x-2x = x^2 -3 -2x
0 = x^2 -2x-3
Factor
0 =(x-3) (x+1)
Using the zero product property
x-3 =0 x+1 =0
x=3 x=-1
- 3 when x = -2?
What is the point on the graph of the function f(x) = (x +
Enter your answer in the boxes.
THESE
Answer:
The point is (-2, -3)
Step-by-step explanation:
Given function:
[tex]f(x)= (x+2)^2-3[/tex]
For: [tex]f(x)=y[/tex] and [tex]x=-2[/tex]
[tex]f(-2)= (-2+2)^2-3\\f(-2)= (0)^2-3\\f(-2)= -3\\[/tex]
∴[tex]y=-3; x=-2[/tex]
I need help I don’t really don’t understand this and the first on I will give you brainlist
Analyze the table below and complete the instructions that follow.
Grey
4
White
Silver
Black
Car
819
Truck
SUV 358
Total
13
118
Total
24
17
19
4
3
60
Let event A be defined as a randomly selected vehicle being silver or black. Let event B be defined as a randomly selected
vehicle being a car or a truck. Find P(NOT BA).
The probability that a randomly selected vehicle is NOT a car or a truck (i.e., it's an SUV) given that it's silver or black is approximately -18.6167.
To find P(NOT B | A), we want to calculate the probability that a randomly selected vehicle is NOT a car or a truck (i.e., it's an SUV) given that it's silver or black.
First, let's find the probabilities of events A and B:
Event A: Probability of a randomly selected vehicle being silver or black.
Event B: Probability of a randomly selected vehicle being a car or a truck.
From the table, we can find the probabilities of A and B:
P(A) = Probability of a silver or black vehicle = (Silver + Black) / Total = (17 + 19) / 60 = 36 / 60 = 3 / 5.
P(B) = Probability of a car or a truck = (Car + Truck) / Total = (819 + 358) / 60 = 1177 / 60.
Now, we can use these probabilities to find P(NOT B | A) using the formula for conditional probability:
P(NOT B | A) = P(A AND NOT B) / P(A)
To find P(A AND NOT B), we need to find the probability of a vehicle being silver or black (A) AND not being a car or a truck (NOT B):
P(A AND NOT B) = P(A) - P(A AND B)
Now, we already have P(A) and P(B), so we can calculate P(A AND B):
P(A AND B) = P(A) * P(B) = (3/5) * (1177/60)
Now, subtract P(A AND B) from P(A) to get P(A AND NOT B):
P(A AND NOT B) = P(A) - P(A AND B)
Finally, we can calculate P(NOT B | A):
P(NOT B | A) = P(A AND NOT B) / P(A)
Plug in the values:
P(NOT B | A) = (P(A) - P(A AND B)) / P(A)
Calculate the values:
P(NOT B | A) = ((3/5) - ((3/5) * (1177/60))) / (3/5)
Simplify the expression:
P(NOT B | A) = (3/5) * (1 - (1177/60)) / (3/5)
Now, perform the calculations:
P(NOT B | A) = (3/5) * (1 - (1177/60)) / (3/5)
P(NOT B | A) = (3/5) * (1 - 19.6167) / (3/5)
P(NOT B | A) ≈ (3/5) * (-18.6167) / (3/5)
P(NOT B | A) ≈ -18.6167
for such more question on probability
https://brainly.com/question/23417919
#SPJ2
Express 150% of 60% as a percent.
Answer:
0.9 ≈ 90%
Step-by-step explanation:
60% = 60/100
150% of 60% = 150/100 * 60/100
= 9000/10000
= 0.9 ≈ 90%
Choose 1 answer:
A. Vertical angles
B. Complementary angles
C. Supplementary angles
D. None of the above
Answer:
D
Step-by-step explanation:
vertical angles are opposite from each other
Complementary angles are 180
supplementary angles are 90
so it is none of the above
6x9 = (6 * 5) + (6
)
What is the missing number
Answer:
*4
Step-by-step explanation:
Answer:
4
6x9=54=(6*5)+(6*4)
Step-by-step explanation:
6x9=54=(6*5)+(6*4)
6x9=54
54 is the number you are trying to get
6*5= 30
so now you need something to add up to 54
6*4=24
24+30=54
Q12: Annette plans to visit an amusement park where she must pay for admission and purchase tickets to go on the rides. Annette wants to find the total cost for a day at the amusement park. She wrote the equation c=1.50x+12 to predict c, the total cost for a day at the amusement park. What could the number 12 represent in Annette’s equation? A the number of rides B the cost of admission C the cost of each ticket D the number of tickets
Answer:
B
Step-by-step explanation:
B because an admission is a constant.
Answer:
C=1.50x+12
Step-by-step explanation:
1 ride with admission is $13.50
2 rides with admission is $15.00
3 rides with admission is $16.50
4 rides with admission is $18.00
It's $1.50(x) difference between each total cost(c) letting us know that is the cost for 1 ticket meaning it cost $12.00 for admission.
help i have more questions
Answer:
A≈49.86
Step-by-step explanation:
Evaluate the arithmetic series described : 2+(-2)+(-6)+(-10)...,510
Theo found the driving distance from Glacier National Park to Yellowstone Park to be 448 miles. Theo used a map that had a ratio of StartFraction 5 centimeters over 320 miles EndFraction. How many centimeters is the distance on the map? Round to the nearest unit if necessary.
4 centimeters
7 centimeters
64 centimeters
90 centimeters
Answer:
7
Step-by-step explanation:
Answer:
B. 7
Step-by-step explanation:
Given the following exponential function, identify whether the change represents
growth or decay, and determine the percentage rate of increase or decrease.
y=9300(0.991)
I'm assuming the function given is y = 9300(0.991)^x
If so, then the base of the exponent 0.991 is in the form 1+r
1+r = 0.991
r = 0.991-1
r = -0.009
The negative r value indicates a percent decrease.
Specifically it is a 0.9% decrease since 0.009 = 0.9/100 = 0.9%
Any time you have a percent decrease like this, the exponential function is undergoing decay.
17 Points! Help Me please!
Answer:
This is the completed table:[tex]\left[\begin{array}{ccccccccccc}trapezoids&1&2&3&4&5&6&10&18&n\\perimeter&10&16&22&28&34&40&64&112&6n+4\end{array}\right][/tex]
for the words and graph please see below and the attached image.
Step-by-step explanation:
Notice that every time you add a trapezoid in the given fashion (attached to the right of the previous figure) yo are adding a net of 6 units (2+4) to the total perimeter (which started in the first figure as 2+2+2+4 = 10).
We can then write the following values to complete the given table:
1 trapezoid , gives perimeter = 1*4 + 3*2 = 10
2 trapezoids, give perimeter = 2*4 + 4*2 = 16
3 trapezoids, give perimeter = 3*4 + 5*2 = 22
4 trapezoids, give perimeter = 4*4 + 6*2 = 28
5 trapezoids, give perimeter = 5*4 + 7*2 = 34
6 trapezoids, give perimeter = 6*4 + 8*2 = 40
10 trapezoids, give perimeter = 10*4 + 12*2 = 64
n trapezoids, give perimeter = n*4 + (n+2)*2 = 4n + 2n + 4 = 6n + 4
Now, given this general relationship for "n" trapezoids, one can find the number of trapezoids that render a perimeter = 112, as required in the table:
6n + 4 = 112
then 6n = 112 - 4 = 108
then n= 108/6 = 18
so 18 trapezoids give a perimeter of 112 (to complete that missing value in the table).
Now, we can plot a general function of similar form of that we got for a collection of n trapezoids but using "x" instead of "n" and having clear in our mind that the values we want to use are only positive integers greater than zero to represent the number of trapezoids:
f(x) = 6x +4
See attached image were the actual valid points are marked as blue dots.